2022
DOI: 10.1186/s13287-022-03015-7
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes from mmu_circ_0001052-modified adipose-derived stem cells promote angiogenesis of DFU via miR-106a-5p and FGF4/p38MAPK pathway

Abstract: Background Diabetic foot ulcer (DFU) is a chronic infectious disease caused by diabetes mellitus (DM). Angiogenesis plays the decisive role in wound healing of DFU. Adipose-derived stem cells (ADSCs) can ameliorate angiogenesis in DFU by exosomes. This study aims to determine the mechanism of exosomes from mmu_circ_0001052-modified ADSCs in angiogenesis of DFU. Methods HUVECs were induced by high glucose and mice stimulated using STZ injection duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(32 citation statements)
references
References 34 publications
2
30
0
Order By: Relevance
“…Several studies have confrmed that many miRNAs participate in the process of wound healing [26][27][28][29]. During the infammatory period of the wound, miRNA-181c and miRNA-21-5p promote the expression of M2 macrophages to inhibit the infammatory response and shorten the infammatory response time [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have confrmed that many miRNAs participate in the process of wound healing [26][27][28][29]. During the infammatory period of the wound, miRNA-181c and miRNA-21-5p promote the expression of M2 macrophages to inhibit the infammatory response and shorten the infammatory response time [30,31].…”
Section: Discussionmentioning
confidence: 99%
“…However, in the diabetic environment, the number and function of these cells are restricted to varying degrees, and the wound-healing process is delayed or interrupted. Studies found that exosomes could greatly promote survival and inhibit the apoptosis of ECs (14)(15)(16)(17), fibroblasts (11), keratocytes (11), and neurons (11). Mostly, exosomes were reported to promote the proliferation, migration, and angiogenesis of endothelial cells, and a variety of pathways were involved, like PI3K/AKT pathway, ERK1/2 pathway, FGF4/p38MAPK pathway and HIPK2 pathway (15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Effect Of Exosomes On Promoting Skin Wound Healing In Diabet...mentioning
confidence: 99%
“…Studies found that exosomes could greatly promote survival and inhibit the apoptosis of ECs (14)(15)(16)(17), fibroblasts (11), keratocytes (11), and neurons (11). Mostly, exosomes were reported to promote the proliferation, migration, and angiogenesis of endothelial cells, and a variety of pathways were involved, like PI3K/AKT pathway, ERK1/2 pathway, FGF4/p38MAPK pathway and HIPK2 pathway (15,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29). This greatly enhances the ability of local vascular regeneration in diabetic wound healing.…”
Section: Effect Of Exosomes On Promoting Skin Wound Healing In Diabet...mentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous proangiogenic factors are produced under hypoxia circumstances. These factors, the most notable of which is VEGF, activate the endothelial cells, stimulate capillaries to form nascent immature loops and branches to provide oxygen and nutrients to the wound site ( 1 , 2 ). Communication between fibroblasts and endothelial cells is essential for skin wound repair and regeneration.…”
Section: Introductionmentioning
confidence: 99%